Development of Learning Media Introduction to Table Tennis Sports Equipment based on Augmented Reality - Al Ilham; Suriyadi Datau; Haerul Ikhsan (Journal Of Sport Education (JOPE), 2024)
This study aims to determine the feasibility of the Jambura Table Tennis (JTT) application which is a product development based on augmented reality in table tennis learning. The development method uses the Multimedia Development Life Cycle (MDLC) model. The stages carried out are: 1) Conceptualizing product ideas through interviews and field observations, 2) Designing the product to be developed, 3) collecting the required materials, 4) Making the product, 5) Alpha and beta testing by media experts and content experts using the Gregory test with 100% validation and individual effectiveness test of 95.4%, small group test with 7 subjects 95.57% and field test of product feasibility with 33 subjects of class X SMA N 1 Dulupi of 89%, 6) Distribution of the Jambura Table Tennis (JTT) application product. From these results it can be concluded that the Jambura Table Tennis (JTT) application product is very valid and feasible for use at SMAN 1 Dulupi. The advantage of this product is that it is more flexible because it can be used on each student's smartphone and does not require data for use, while the weakness of the product is that it only discusses material about introducing table tennis equipment.